2012
DOI: 10.1007/s12195-012-0258-3
|View full text |Cite
|
Sign up to set email alerts
|

Elastic Coupling Effects in Cooperative Transport by a Pair of Molecular Motors

Abstract: Abstract-Engineered constructs coupling a defined number of molecular motors provide an opportunity to study the cooperative transport of cargoes. Theoretical descriptions for the dynamics of such complexes can help to understand experimental data or to quantitatively formulate expectations for such experiments and provide a general framework for such analysis. Here, we review and extend recent theoretical studies that focused on pairs of molecular motors to study effects of coupling between the motors. We der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 64 publications
6
33
0
Order By: Relevance
“…(i) The average velocity and the effective diffusion coefficient of the motor cargo assembly reduces with increase of the elastic coupling constant κ. Our results are consistent with some of the observations made in earlier studies [25,26] where it was reported that, the average cargo velocity reduces as a function of stiffness of the motor-cargo linker. (ii) Asymptotically, the average velocity becomes independent of motor number N while the effective diffusion constant decreases as 1/N .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…(i) The average velocity and the effective diffusion coefficient of the motor cargo assembly reduces with increase of the elastic coupling constant κ. Our results are consistent with some of the observations made in earlier studies [25,26] where it was reported that, the average cargo velocity reduces as a function of stiffness of the motor-cargo linker. (ii) Asymptotically, the average velocity becomes independent of motor number N while the effective diffusion constant decreases as 1/N .…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have appeared in the last few years, based (mostly) on Hookean spring-like interaction between motor and the cargo [19,20,21,22,23,24,25,26,27,28,29]. In Kunwar et al [20], along with elastic interaction among the motors, non-linear force-velocity relations are assigned to different motors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these studies could not explain the experimental observations that two coupled kinesins pull each other from the filament, but move with a velocity that is close to the velocity of a single motor [22]. This interference effect has been studied theoretically by explicitly considering the coupling between the motors not only for kinesin, but also for dynein and myosin motors [11,17,34,35], In general, depending on the single motor dynamics and the elastic coupling, motor pairs can exhibit four different transport regimes [11], The emergence of these distinct regimes can be understood from intuitive time scale arguments that were derived for transport in the absence of an external load force [11,36],…”
Section: Introductionmentioning
confidence: 99%
“…However, most of these studies focused on only a single molecule. Recently, there have been many studies of the cooperative function of multiple motor proteins, as the importance of cooperativity is a hot topic in biophysics [11][12][13][14]. To further understand the physicochemical mechanism of protein functioning, attention is now shifting upward through the hierarchy, from individual elements to the cooperative behavior of the supramolecular system, suggesting the need of an additional technique that transcends conventional single-molecule measurement.…”
Section: Introductionmentioning
confidence: 99%